Deconstructions of subjectivity and responsibility: Jacques Derrida's eco-political and bioethical thought - DiBartolomeo, Jody (University of Ottawa (Canada), 2003)
The first chapter explains Derrida's notion of the trace as the opening of subjectivity to alterity. Autonomy must be rethought as a heteronomic relation with nonhuman others---beings of the world, ecosystems, etc. The second chapter explains the ethical relevance of Husserl's thought for Derrida's project. The third chapter explains many of the implications of Derrida's thought in Of Grammatology. Some of the distinctions between humans and other animals are rethought. In the fourth chapter, Derrida opens Rousseau's conceptions of pity and justice to include nonhuman animals. Next, the deconstruction of Being-towards-death has many implications, such as opening Dasein's responsibility to nonhuman animals. Chapter six claims that we must move beyond the duty of Kant. We must do so in order to be more responsible to the uniqueness of the other, including other cats and horses. Finally, the essential condition of the opening of the ethical and the political is the affirmation of nature and animality, contrary to the thought of Hegel.
Keywords: Philosophy.